KUCING PALING BUSUK - Ain Maisarah, 1982-; Danial Haikal (Bandar Baru Nilai, Negeri Sembilan : KOMIKAW PLT, 2018)
It's full of colors, full of ways to keep cats, manners to care for pets, and a cute cat story.
Targeted at readers level 1, aged 7 years to 9 years.
Keywords: Malay language -- Readers -- Fiction; Malay language -- Readers -- Juvenile literature; Cat stories -- Fiction